Word Sense Disambiguation Using an Evolutionary Approach - Menai, Mohamed El Bachir (Informatica, 2014)
Word sense disambiguation is a combinatorial problem consisting in the computational assignment of ameaning to a word according to a particular context in which it occurs. Many natural language processingapplications, such as machine translation, information retrieval, and information extraction, require thistask which occurs at the semantic level. Evolutionary computation approaches can be effective to solvethis problem since they have been successfully used for many NP-hard optimization problems. In thispaper, we investigate main existing methods for the word sense disambiguation problem, propose a geneticalgorithm to solve it, and apply it to Modern Standard Arabic. We evaluated its performance on a largecorpus and compared it against those of some rival algorithms. The genetic algorithm exhibited moreprecise prediction results.